Small Scale Unmanned Underwater Remotely Operated Crawler (ROC) - Mohd Shahrieel Mohd Aras; Muhammad Nizam Kamarudin; Muhammad Hanif Bin Che Rusli; Muhammad Iktisyam Mohd Zainal (Institute of Advanced Engineering and Science, 2016)
This project is describes the development of underwater vehicle which is remotely operated crawler (ROC). The ROC is developed for the implementation of underwater surface floor and used as for rescuing application. This project is aim to reduce the risk the human life and to solve the disability of human to dive to the underwater for rescue and archeologist work in a longer period. Due to the underwater vehicle that can be operated in a larger depth and reducing the liability of the human life. Moreover, the main problem with this ROC application is to travelling under the uneven of the underwater floor and make sure it always have negative buoyant and a good stability to perform at uneven surface of underwater. Furthermore, the ROC need the overcome the obstacle of the underwater surface without any problem. Therefore, the design of ROC is based on four wheel mechanism to maneuver it at the uneven surface. Besides that, the ROC is tethered and control manually by using a joystick controller and the Peripheral Interface Controller (PIC) are used to control this ROC. This method is to fulfill the target of the project that are to develop and fabricate the ROC and to study the performance of the ROC in terms of controllability, stability and maneuverability. As a result, the movement of ROC is analyzing in order to gain the requirement of stability and the buoyancy in the water. Moreover, the development of the ROC can be tested in several experiments which includes overcome obstacle, controllability, and it performances to be operated on the surface floor of underwater. Hence, this project will gives the good impact and benefit related to the underwater industries and can be applied in the rescuing application in the future.